Demonstrating the dual functionalities of CeO2–CuO composites in solid oxide fuel cells. (26th February 2021) - Akbar, Muhammad; Tu, Zhengwen; Jin, Bin; Mushtaq, Naveed; He, Zili; Dong, Wenjing; Wang, Baoyuan; Wang, Xunying; Xia, Chen
Abstract: Nowadays, lowering the operating temperature of solid oxide fuel cells (SOFCs) is a major challenge towards their widespread application. This has triggered extensive material studies involving the research for new electrolytes and electrodes. Among these works, it has been shown that CeO2 is not only a promising basis of solid oxide electrolytes, but also capable of serving as a catalytic assistant in anode. In the present work, to develop new electrolytes and electrodes for SOFCs based on these features of CeO2, a new type of functional composite is developed by introducing semiconductor CuO into CeO2 . The prepared composites with mole ratios of 7:3 (7CeO2 –3CuO) and 3:7 (3CeO2 –7CuO) are assessed as electrolyte and anode in fuel cells, respectively. The cell based on 7CeO2 –3CuO electrolyte reaches a power outputs of 845 mW cm −2 at 550 °C, superior to that of pure CeO2 electrolyte fuel cell, while an Ce0.8 Sm0.2 O2-δ electrolyte SOFC with 3CeO2 –7CuO anode achieves high power density along with open circuit voltage of 1.05 V at 550 °C. In terms of polarization curve and AC impedance analysis, our investigation manifests the developed 7CeO2 –3CuO composite has good electrolyte capability with a hybrid H + /O 2− conductivity of 0.1–0.137 S cm −1 at 500–550 °C, while the 3CeO2 –7CuO composite plays a competent anode role with considerable catalytic activity, indicative of the dual-functionalities of CeO2 –CuO in fuel cell. Furthermore, a bulk heterojunction effect based on CeO2 /CuO pn junction is proposed to interpret the suppressed electrons in 7CeO2 –3CuO electrolyte. Our study thus reveals the great potential of CeO2 –CuO to develop functional materials for SOFCs to enable low-temperature operation. Highlights: New semiconducting-ionic CeO2 –CuO composites are developed for LT-SOFCs. 7CeO2 –3CuO has good electrolyte function with high hybrid H + /O 2− conductivity. 3CeO2 –7CuO exhibits good anode reaction activity. Fuel cells based on CeO2 –CuO electrolyte and anode achieve high performance.